2008
DOI: 10.1128/aac.01075-07
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activities of Voriconazole, Itraconazole, and Terbinafine Alone or in Combination against Pythium insidiosum Isolates from Brazil

Abstract: We evaluated the in vitro activities of voriconazole, itraconazole, and terbinafine against 30 clinical isolates of Pythium insidiosum using a checkerboard macrodilution method. The combined activity of terbinafine plus itraconazole or plus voriconazole was synergic against 17% of the strains. Antagonism was not observed.Pythium insidiosum is classified in the kingdom Stramenopila, class Oomycetes (3). It causes pythiosis, a disease mainly diagnosed in horses, dogs, and humans (14). Human pythiosis was first d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
37
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 18 publications
5
37
1
2
Order By: Relevance
“…Our findings agree with those of previous reports that show in vitro synergy between azoles and terbinafine for Zygomycota, Fonsecaea pedrosoi, Cladophialophora carrioni, Phialophora verrucosa, and Scedosporium, Pythium, and Aspergillus species (2,7,14,19,22). Other authors also reported good interactions between terbinafine and amphotericin B against Zygomycota (7).…”
supporting
confidence: 82%
See 3 more Smart Citations
“…Our findings agree with those of previous reports that show in vitro synergy between azoles and terbinafine for Zygomycota, Fonsecaea pedrosoi, Cladophialophora carrioni, Phialophora verrucosa, and Scedosporium, Pythium, and Aspergillus species (2,7,14,19,22). Other authors also reported good interactions between terbinafine and amphotericin B against Zygomycota (7).…”
supporting
confidence: 82%
“…There are some in vitro studies, most using the checkerboard method, that confirm these findings, with lower MICs against a large variety of fungi, such as Aspergillus spp., Candida spp., Mucorales spp., Pythium insidiosum, Scedosporium prolificans, Paecilomyces spp., dermatophytes, and zygomycetes (2,3,7,14,15,22).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Combinations of antifungal agents against pythiosis have not been thoroughly studied, and therefore, such in vitro combinatory activities against P. insidiosum require attention (1,6).…”
mentioning
confidence: 99%